Immunosuppressive treatment combined with nucleoside analog is superior to nucleoside analog only in the treatment of severe thrombocytopenia in patients with cirrhosis associated with hepatitis B in China: A multicenter, observational study. (3rd October 2015) - Zhang, Xiao Hui; Feng, Ru; Xu, Lan Ping; Jiang, Qian; Jiang, Hao; Fu, Hai Xia; Liu, Hui; Niu, Ting; Wang, Xin; Hu, Jian Da; Jiang, Ming; Wang, Zhao; et al.
Abstract: No effective treatment has been identified for patients of liver cirrhosis (LC) associated with hepatitis B virus (HBV) and severe thrombocytopenia. We aimed to explore the effectiveness and safety of low-dose prednisone or cyclosporine A (CsA) combined with nucleoside analog (NA) in patients with severe thrombocytopenia associated with HBV-related LC. We included 145 consecutive compensated HBV-associated LC patients with severe thrombocytopenia between 1 January 2006 and 31 December 2013. We divided the patients into three groups by treatment strategy, including NA only ( n  = 57), NA plus prednisone ( n  = 46), and NA plus CsA ( n  = 42). We analyzed the platelet counts, bleeding events, liver function, replication of HBV, and outcomes in each group. At all time points during this observation, the platelet counts in prednisone or CsA group were higher than those in the NA only group. There are significant differences in the cumulative rates of bleeding events among the three groups. The platelet counts and treatment were factors associated with bleeding events in multivariate analysis. The differences in HBV-DNA negative rates, HBV-DNA elevated rates, normal serum alanine transaminase rates, serum alanine transaminase elevated more than two times the baseline rates, and HBeAg seropositive conversion ratio among the groups did not reach statistical significance. The adverse events in our study were, in general, mild and balanced among the three treatment groups. Treatment with low-dose prednisone or CsA plus NA could elevate the platelet counts and reduce the risk of bleeding events in HBV LC with severe thrombocytopenia.